2014
DOI: 10.1007/s13524-014-0355-0
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Decline and Child Schooling in Urban Settings of Burkina Faso

Abstract: As evidenced in Western rich countries, Asia, and Latin America, lower fertility allows couples to invest more in each of their children's schooling. This postulate is the key rationale of family planning policies in sub-Saharan Africa. Yet, most studies on Africa have found no correlation or even a positive relationship between the number of children in a family and their educational attainment. These mixed results are usually explained by African family solidarity and resource transfers that might reduce pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…An additional child of the mother increases the intensity of child poverty by 0.022 and 0.025 in 2008 and 2014 respectively. These results are consistent with findings from previous studies including Angrist et al (2010), Black et al (2010), Dang and Rogers (2015) and Bougma et al (2015) that report such child quantity and quality trade-offs.…”
Section: Determinants Of Intensity Child Poverty In Ghanasupporting
confidence: 93%
See 1 more Smart Citation
“…An additional child of the mother increases the intensity of child poverty by 0.022 and 0.025 in 2008 and 2014 respectively. These results are consistent with findings from previous studies including Angrist et al (2010), Black et al (2010), Dang and Rogers (2015) and Bougma et al (2015) that report such child quantity and quality trade-offs.…”
Section: Determinants Of Intensity Child Poverty In Ghanasupporting
confidence: 93%
“…Dang and Rogers (2015) for example shows that increased fertility reduces parental investments in human capital of children in Vietnam. Bougma et al (2015) also report similar negative effect of sibship size on school achievement in Burkina Faso. Further, in a study of India, Azam and Saing (2018) find a quality-quantity trade-off for some child outcomes.…”
Section: Determinants Of Intensity Child Poverty In Ghanasupporting
confidence: 55%
“…A range of other instruments have been proposed, including infertility (Bougma et al ., 2015), miscarriage (Hotz et al ., ; Maralani, ; Miller, ) and distance to family planning (Dang and Rogers, ). The outcomes and empirical results related to these studies are displayed in Table .…”
Section: The Effects Of Family Size On Childrenmentioning
confidence: 99%
“…A few researchers found a negative relationship between family size and educational attainment. These include Baez (2008), Rosenzweig and Zhang (2009), Bagger et al (2013), Dumas and Lefranc (2013), Bougma et al (2015) and Kugler and Kumar (2015). Blaabaek et al (2017) adopted a different approach and argue that from a causality centered point of view, previous research studies that had found a negative relationship between family size and educational attainment were invalid.…”
Section: Discussionmentioning
confidence: 99%